2010
DOI: 10.3892/ijmm.2010.549
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of inhibitory millimeter wave treatment effects on the TNF-α-induced NF-κB signal transduction pathway

Abstract: Abstract. Abnormal activation of the nuclear factor-κB (NF-κB) in chondrocytes initiates the transcription of inflammatory mediators, promotes their generation and release, and amplifies initial inflammatory signals. This results in the release of chondral matrix-degrading enzymes and accelerates the degeneration of articular cartilage. As a non-pharmaceutical and non-invasive physical therapy regimen, millimeter wave treatment has been successfully used for the treatment of osteoarthritis. In this study, chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Our preliminary work demonstrated that MW inhibits the activation of the TNF- α -mediated NF- κ B signal transduction pathway [ 13 ]. To further discover the millimeter wave's mechanism of action, we used TNF- α to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary work demonstrated that MW inhibits the activation of the TNF- α -mediated NF- κ B signal transduction pathway [ 13 ]. To further discover the millimeter wave's mechanism of action, we used TNF- α to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter wave is a high-frequency electromagnetic wave at a wavelength from 1-10 mm and a frequency of 300 million cycles/sec (300 MHz) to 300 billion cycles/second (300 GHz) (10,11). The millimeter waves within living organisms generate 0.5x10 10 -3x10 12 coherent oscillations during metabolism, which can be absorbed by biological tissues through resonance to produce a non-thermal biological effect (12).…”
Section: Introductionmentioning
confidence: 99%
“…On several in vitro models have shown that inhibition and reduced activity of NF-κB is associated with decreasing of MTT reduction, which shows that there is cytotoxic, apotototic and/or antiproliferative effect (30,31). Our treatments have generally shown that decrease of NF-κB activity went along with the decline of MTT test values.…”
Section: Discussionmentioning
confidence: 82%